The Crisis of the 14th Century - Bauch, Martin; Jasper Schenk, Gerrit (Das Mittelalter. Perspektiven mediävistischer Forschung. Beihefte, 2020)
Societal and environmental change not only coincide during the period 1250-1380, they interact: What has been long discussed as the 'Crisis of the 14th Century' is happening during a shifting climatic regime, from the Medieval Climate Anomaly to the onset of the Little Ice Age. The volume highlights this 'teleconnections' between environment and society with a set of interdisciplinary and regionally diverse contributions on Europe and beyond.